Measuring hidden Higgs and strongly-interacting Higgs scenarios - Bock, Sebastian; Lafaye, Rémi; Plehn, Tilman; Rauch, Michael; Zerwas, Dirk; Zerwas, Peter M. (Physics letters, 2010)
Higgs couplings can be affected by physics beyond the Standard Model. We study modifications through interactions with a hidden sector and in specific composite Higgs models accessible at the LHC. Both scenarios give rise to congruent patterns of universal, or partially universal, shifts. In addition, Higgs decays to the hidden sector may lead to invisible decay modes which we also exploit. Experimental bounds on such potential modifications will measure the concordance of an observed Higgs boson with the Standard Model.